THE EFFECT OF SPORT MASSAGE TOWARD THE DECREASE OF FATIGUE - Ni Eka Dewi Ambarawati; I Made Jawi; I Made Muliarta; Ni Made Linawati; Anak Agung Sagung Sawitri; I Made Krisna Dinata (Sport and Fitness Journal, 2021)
ABSTRACT Background: Fatigue is a process of decreasing tolerance to physical activities. Metabolism burns energy where it breaks down carbohydrates to become lactic acid which results in fatigue. There are many ways to treat fatigue, such as sports massage. Objective: This research will guide the effect of sports massage on decreasing fatigue of Indonesia’s water ski athletes. Method: Research method Treatment By Subject Design. The population of this study were all Indonesian athletes in overall water skiing who were still active in 2019. The subjects of the study were 18 Indonesian athletes of overall water skiing and divided into two different treatment periods. Period 1 was given sports massage treatment and Period 2 was given active rest treatment, between treatments was given a break for 3 days, so the research lasted for 5 days. Lactic acid measurement is measured by taking a blood sample and measured using an accurted lactate tool. Result: Based on the test result, we find that the mean of lactic acid levels before sport massage was 7.2333 ± .99173, and after sport massage was 3.1333 ± .70711 mmol/L. Mean of lactic acid before active rest was 7.2889 ± .67116 mmol/L, and after active res was 4.4061 ± .82253 mmol/L. Differential test result of lactic acid levels before treatment in between the second period treatment with Paired sample t-test showed a significance value of the second period p=0.791 (p>0.05). The value stated there was no significant difference before treatment. Differential Test of Lactic Acid Level Reduction after treatment in between the Two Periods with Paired sample t-test showed that p=0.00 (p<0.05) which means that the two periods have a significant difference. When viewed from the average difference before and after sport massage treatment was 4.1000 ± .77763 mmol/L, while the difference before and after active resting treatment was 2.8828± .53714mmol/L can be concluded that the sport massage treatment is more effective in reducing levels of lactic acid compared to active rest. Conclusion: Sport massage and active rest can both reduce levels of lactic acid, but sport massage is more effective than active rest. Suggestion: The suggenstion in this study is that the trainers are expected to be able to provide a good recovery method after the athlete has done the exercise. Keywords: Fatigue, Sports Massage, Lactic Acid